Safe Harbor or Muddy Waters. - Barrett, M. Edgar; Shaw, Wayne H. (The Accounting Review, 1987)
ABSTRACT: In 1981, Congress enacted a "safe harbor" lease law that permitted firms to sell unneeded tax depreciation deductions and tax credits to other firms. During the effective life of the law, the Financial Accounting Standards Board (FASB) did not establish reporting or disclosure requirements for firms entering the safe harbor transactions. Because of this, many policies were followed. This paper examines the impact of this lack of reporting and disclosure guidance on the comparability and Interpretability of financial statements across firms involved in leasing. This study provides examples of problems the FASB might need to address when analyzing changes under the new tax bill.